MioLab, a rat cardiac contractile force simulator: Applications to teaching cardiac cell physiology and biophysics. Issue 3 (December 2015) - da Silva, Robson Rodrigues; Bissaco, Marcia Aparecida Silva; Goroso, Daniel Gustavo
Highlights: Highlight the didactic resources of a simulator MioLab ® . Tool that complements the study of the physiology and biophysics of the cardiac cell. Learning activities simulating experiments in silico. Inhibition of ATPase Ca 2+ of the cardiac sarcoplasmic reticulum – studies in silico. Abstract: Introduction: Understanding the basic concepts of physiology and biophysics of cardiac cells can be improved by virtual experiments that illustrate the complex excitation–contraction coupling process in cardiac cells. The aim of this study is to propose a rat cardiac myocyte simulator, with which calcium dynamics in excitation–contraction coupling of an isolated cell can be observed. This model has been used in the course "Mathematical Modeling and Simulation of Biological Systems". In this paper we present the didactic utility of the simulator MioLab ® . Methods: The simulator enables virtual experiments that can help studying inhibitors and activators in the sarcoplasmic reticulum sodium–calcium exchanger, thus corroborating a better understanding of the effects of medications, which are used to treat arrhythmias, on these compartments. The graphical interfaces were developed not only to facilitate the use of the simulator, but also to promote a constructive learning on the subject, since there are animations and videos for each stage of the simulation. The effectiveness of the simulator was tested by a group of graduate students. Results: Some examples of simulations were presented in order to describe the overall structure of the simulator. Part of these virtual experiments became an activity for Biomedical Engineering graduate students, who evaluated the simulator based on its didactic quality. As a result, students answered a questionnaire on the usability and functionality of the simulator as a teaching tool. All students performed the proposed activities and classified the simulator as an optimal or good learning tool. In their written questions, students indicated as negative characteristics some problems with visualizing graphs; as positive characteristics, they indicated the simulator's didactic function, especially tutorials and videos on the topic of this study. Conclusions: The results show that the simulator complements the study of the physiology and biophysics of the cardiac cell.